2019
DOI: 10.1002/nag.3032
|View full text |Cite
|
Sign up to set email alerts
|

A bounding surface model for anisotropically overconsolidated clay incorporating thermodynamics admissible rotational hardening rule

Abstract: Summary A bounding surface model is formulated to simulate the behavior of clays that are subject to an anisotropic consolidation stress history. Conventional rotational hardening is revisited from the perspective of thermodynamics. As the free energy cannot be accumulated infinitely upon critical state failure, the deviatoric back stress must vanish. This requires the rotated yield surface to be turned back to eventually align on the hydrostatic axis in the stress plane. Noting that most of the previous propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 61 publications
1
43
0
Order By: Relevance
“…Jiang et al 38 . presented RH rules as a function of plastic volumetric strain increment, Chen and Yang 17 introduced a RH rule by incorporating only plastic deviatoric strain increment. Involving both components of plastic strain increment in the evolution of anisotropy is another option that can be found in the works of Pestana and Whittle 19 , Wheeler et al 36 ,.…”
Section: Model Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Jiang et al 38 . presented RH rules as a function of plastic volumetric strain increment, Chen and Yang 17 introduced a RH rule by incorporating only plastic deviatoric strain increment. Involving both components of plastic strain increment in the evolution of anisotropy is another option that can be found in the works of Pestana and Whittle 19 , Wheeler et al 36 ,.…”
Section: Model Formulationmentioning
confidence: 99%
“…Yu 18 showed that models using associated flow rule fail to predict the undrained response of normally consolidated undisturbed clays with softening and pre‐failure peak strengths. Taking this point into account, several recently developed models employ the non‐associated flow rule in their formulation 16,17,37–39,52 …”
Section: Model Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…A new parameter that controls the shape of the yield surface was introduced in the model to fit the undrained shear strength. Chen and Yang 27 proposed a bounding surface model for overconsolidated clays to simulate elastoplastic deformations. With a modified yield surface, the model can capture the contractive or dilative response and hardening or softening behavior under different conditions.…”
mentioning
confidence: 99%